Study on the preparation, characterization of a novel solid Lewis acid Al3+-SO42−/MWCNTs catalyst and its catalytic performance for the synthesis of biodiesel via esterification reaction of oleic acid and methanol. (1st December 2017) - Shu, Qing; Tang, Guoqiang; Liu, Fengsheng; Zou, Wenqiang; He, Jiangfan; Zhang, Caixia; Zou, Laixi
Graphical abstract: Oxygen-containing groups and carboxyl groups was produced and existed in the tube wall after MWCNTs was oxidized by concentrated sulfuric acid at high temperature. Then hydroxyl and carboxyl groups are sulfonated by sulfuric acid. H + will be substituted by Al 3+ due to the strong metallic property of Al 3+, and then bonded with O 2− . The Lewis acid center is produced at the site of Al 3+ under the electronic effect of SO, which increases the Lewis acidity of the Al 3+ -SO4 2− /MWCNTs catalyst. Highlights: A novel solid Lewis acid catalyst Al 3+ -SO4 2− /MWCNTs. Formation of Lewis acid center related with strong metallic property of Al 3+ . Suitable for synthesis of biodiesel via esterification with high catalytic activity. Abstract: A novel solid Lewis acid catalyst Al 3+ -SO4 2− /MWCNTs was prepared by impregnating multi walled carbon nanotubes (MWCNTs) with concentrated sulfuric acid and Al 3+ . The physical and chemical properties of Al 3+ -SO4 2− /MWCNTs was characterized by X-ray diffraction, transmission electron microscopy, Raman spectroscopy, X-ray fluorescence spectroscopy, NH3 temperature programmed desorption, X-ray photoelectron spectroscopy and pyridine adsorption IR spectra. The catalytic activities of SO4 2− /MWCNTs, Al 3+ -SO4 2− /MWCNTs and Al 3+ -SO4 2− /SWCNTs, Al 3+ -SO4 2− /C were compared when they were respectively applied for the catalytic synthesis of biodiesel via esterification reaction of oleic acid and methanol. Results showed that Al 3+ -SO4 2− /MWCNTs had the highest catalytic activity: the conversion ratio of oleic acid reached 95% when reaction temperature was 65 °C, mass ratio of catalyst to reactants was 0.9 wt% and molar ratio of methanol to oleic acid was 12:1 after 7 h. The high catalytic activity of Al 3+ -SO4 2− /MWCNTs can be ascribed to the flow and escape of electronic is very easily in the tubular structure of MWCNTs since it has low C1s binding energy. It will stimulate a strong interaction between Al 3+ and SO4 2−, accompanied with the formation of a stable coordination bond, which increased the crystallization degree of Al 3+ -SO4 2− /MWCNTs catalyst and improved the combination stability of SO4 2− and MWCNTs. In addition, SO band can exert strong electron induced effect, which leads to the increasing of the valence electron layer density of Al element, reduces the shielding effect of outer electrons on core electrons and increases the binding energy of core electrons. It directly affects the electronic state of S and Al and changes the chemical state of SO4 2−, enhances the absorption capacity of Al 3+ and increases the imbalance of the system. Eventually, it changed the original acidity of the Al 3+ -SO4 2− /MWCNTs catalyst and enhanced its Lewis acidity. Hence, the acid site of Al 3+ -SO4 2− /MWCNTs is mainly comprised by Lewis acid, which is favorable for the avoiding of the occurrence of hydration of Brönsted acid active sites.